Optimization of process parameters in preparing nanoemulsion containing kojic monooleate using response surface methodology and evaluation of tyrosinase inhibition through in vitro and in silico methods - Roselan, Muhammad Azimuddin (2020)
Kojic monooleate (KMO), synthesized from the esterification of kojic acid (KA) and oleic acid, has shown a better depigmenting effect than KA. Previously, our research group had successfully loaded KMO into a nanoemulsion system. The composition of each ingredient was then optimized using mixture experimental design (MED) that resulted in a droplet size of 110.01 nm. Although the nanoemulsion was in nano-sized range, they found that the nanoemulsion only stable at the temperature of 4 and 25°C, and unstable at the temperature of 45°C. Thus, this study aims to further optimize the process parameters in producing the nanoemulsion containing KMO using response surface methodology (RSM). The effects of time of high shear (5-20 min), speed of high shear (4500-6500 rpm), and speed of stirrer (200-300 rpm) were investigated. The optimized process parameters in producing the nanoemulsion containing KMO with nano-sized range were 8.04 min (time of high shear), 4905.41 rpm (speed of high shear) and 271.82 rpm (speed of stirrer). The optimized nanoemulsion containing KMO showed good agreement between predicted droplet size (103.71 nm) and actual droplet size (103.97 ± 0.13 nm) with residual standard error (RSE) value less than 2.0%. An analysis of variance (ANOVA) showed that the fitness of the quadratic polynomial fit the experimental data with large F-values (148.79) and small p-values (p<0.0001) and an insignificant lack-of-fit. The physicochemical characterization showed that the optimized nano-emulsified KMO was in the nanosize range (103.97 ± 0.13 nm) and had a zeta potential of -45.4 ± 0.05 mV and a polydispersity index (PDI) of 0.312 ± 0.14, indicating that the nanoemulsion produced was stable, and classified as monodispersed. The pH and conductivity of the optimized nanoemulsion (3.98 ± 0.05 mS/cm) signifying the oil-in-water (O/W) nanoemulsion characteristic. A morphology study revealed that the oil droplets in the optimized nanoemulsion containing KMO were spherical in shape, without any aggregation. In addition, the rheological behavior of the optimized nanoemulsion revealed that the nanoemulsion exhibited shear thinning and non-Newtonian behavior. The optimized nanoemulsion containing KMO remained stable under a centrifugation test and storage stability at different storage temperatures of 4, 25 and 45 °C over 90 days. The MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide) assay performed on the normal 3T3 cell lines showed that the nanoemulsion containing KMO was not cytotoxic with IC50 (concentrations of sample required to inhibit the cell viability by 50%) more than 500 μg/mL (IC50>500 μg/mL). The tyrosinase inhibitory assay revealed that the nanoemulsion containing KMO inhibited tyrosinase activity with the IC50 value of 68.20 μg/mL, compared to the positive control (KA) with the IC50 value of 124.28 μM. The permeation study revealed that 45.94 ± 0.03% of KMO was released from the nanoemulsion and able to permeate the cellulose acetate membrane after 8 h of study time. The total KMO permeated across the membrane per unit area after 8 h of study time was 14355.21 μg.cm-2, with the flux (J) of 1757.1 μg.cm-2.h-1 and permeation coefficient (Kp) value of 0.09 cm.h-1. The kinetic mechanism analysis revealed that the permeation data was most fitted with the zeroth-order model. In silico molecular docking revealed that the binding energy for the KMO against mushroom tyrosinase (PDB ID: 2Y9X) is -5.70 kcal/mol, stronger than KA with the binding energy of -4.01 kcal/mol. The interaction of KMO on mushroom tyrosinase is via hydrophobic interaction involving His61, His85, Glu256, His259, Asn260, His263, Phe264, Met280, Gly281, Ser282, Val283, and Ala286 residues. These results predicted that KMO may inhibit mushroom tyrosinase. In conclusion, the nanoemulsion containing KMO with nano-sized range, good stability and physicochemical properties with potent tyrosinase inhibitor properties was successfully optimized in this study.